2014
DOI: 10.1101/cshperspect.a019653
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Pharmacokinetics and Pharmacodynamics

Abstract: Successful treatment of infectious diseases requires choice of the most suitable antimicrobial agent, comprising consideration of drug pharmacokinetics (PK), including penetration into infection site, pathogen susceptibility, optimal route of drug administration, drug dose, frequency of administration, duration of therapy, and drug toxicity. Antimicrobial pharmacokinetic/pharmacodynamic (PK/PD) studies consider these variables and have been useful in drug development, optimizing dosing regimens, determining su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 183 publications
1
68
0
2
Order By: Relevance
“…1D (27). For amphotericin B, the data for C. auris were also remarkably congruent with prior studies, which have shown stasis to occur at C max /MIC exposures of 1 to 2 (27). The stasis C max /MIC for the groups of C. auris strains in this study was near 1.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…1D (27). For amphotericin B, the data for C. auris were also remarkably congruent with prior studies, which have shown stasis to occur at C max /MIC exposures of 1 to 2 (27). The stasis C max /MIC for the groups of C. auris strains in this study was near 1.…”
supporting
confidence: 80%
“…The reasons for the enhanced efficacy observed for micafungin against C. auris compared to those of fluconazole and amphotericin B are unknown and an important area for future investigation. Importantly, targets identified in this model with triazoles and echinocandins have correlated well with clinical outcomes in patients with invasive candidiasis (27). Thus, the present findings in this PK/PD study should be useful for forecasting effective treatment regimens for patients and in the development of preliminary susceptibility breakpoints.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…This is consistent with AUC/MIC ratio as the pharmacodynamically linked index and supports our findings. The importance of the AUC/MIC ratio index for this compound with concentration-independent killing is reminiscent of PK/PD characteristics of the oxazolidinones and triazoles (24)(25)(26). One reason for this observed outcome in our dose fractionation study could be due to postantibiotic effects (PAEs).…”
Section: Figmentioning
confidence: 88%
“…Pharmacokinetic data indicate that PUR1900 results in higher and more sustained lung exposure of itraconazole relative to oral dosing, an important factor in the activity of itraconazole against Aspergillus. In addition, plasma exposure following PUR1900 inhalation was substantially lower than that with oral dosing, potentially decreasing risks of systemic itraconazole‐related AEs and drug–drug‐interactions. Finally, the sustained nature of lung exposure and the relatively low accumulation with repeat dosing supports once daily dosing in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%